Enhancing aerobic endurance in football players through high-intensity interval training and a game-based approach - Arjun Pamungkas; Setiyawan; Danang Aji Setyawan (Sriwijaya Journal of Sport, 2026)
Research Background: Aerobic endurance is important in soccer because the game requires high-intensity activity with quick recovery. However, training at the school level is often not based on a balanced scientific approach. Research Objectives: This study aims to analyze and compare the effects of High-Intensity Interval Training (HIIT) and the Game-Based Approach on aerobic endurance. Method: This study used a quasi-experimental design with a pretest-posttest control group. The sample consisted of 20 students participating in a soccer extracurricular program, divided into two groups and trained for 12 sessions. Aerobic endurance was measured using the Bleep test. Data were analyzed using paired and independent sample t-tests (α = 0.05). Results: Both training methods significantly improved aerobic endurance (p < 0.05). However, there was no significant difference between the two groups. Conclusion: HIIT and the Game-Based Approach are equally effective in improving aerobic endurance and can be applied based on students’ needs and characteristics.